Elegant security: Concept, evidence and implications. (September 2022) - Farrell, Graham; Tilley, Nick
Some security devices can be ugly, inconvenient or an infringement on civil liberties. This means that security is a quality of life issue as well as one of crime prevention. Here we propose that, in addition to preventing crime and being cost effective, security should preferably be ethical and unobtrusive, aesthetically neutral or pleasing, and the easy-to-use or default option. We describe security with such characteristics as 'elegant'. We use two case studies to explore how, as many types of crime have declined in recent decades, there was an increase in elegant and a decrease in inelegant security. We suggest that the lifecycle of some security technologies sees them evolve from inelegant to elegant, that continual improvement is required to keep ahead of offender adaptations, and that inelegant security can fall into disuse even if it prevents crime. It is hoped that this conceptual contribution might inform discussions about the appropriate form and role of security.